Historical dictionary of East Timor - Gunn, Geoffrey C. (Historical dictionaries of Asia, Oceania, and the Middle East ;, 2011)
East Timor, also known as Timor-Leste, comprises the eastern half of the island of Timor, located at the eastern end of the Indonesian archipelago. East Timor was among the last of colonial territories to become independent, and it actually had to be liberated twice. First, after more than four centuries of Portuguese colonial rule, it achieved independence in 1975 only to be invaded and occupied by Indonesia. After a blood-soaked occupation of 24 years and following intense international pressure, the Jakarta-regime only grudgingly allowed East Timor to form a nation of its own in 1999. Since then, the new state has faced further armed clashes and is only now able to seriously engage in nation-building. Historical Dictionary of East Timor relates the turbulent history of this country through a chronology, an introductory essay, an expansive bibliography, and over 200 cross-referenced dictionary entries on significant persons, events, places, organizations, and other aspects of East Timor history from the earliest times to the present.